USE OF THE L-ARGININE IN A COMPLEX OF THERAPY OF PATIENTS WITH CHRONIC KIDNEY DESEASE IN COMBINATION WITH CORONARY HEART DISEASE - Potyazhenko, M.M.; Cradle, N.A.; Sokolyuk, N.L.; Haymenova, G.S.; Gajewski, S.A. (World of Medicine and Biology, 2014)
The aim of our study was to estimate the efficiency of L-arginine during the corrections of endothelial dysfunction in patients with chronic kidney disease (CKD) ІІ and ІІІ stages in combination with coronary heart disease (CHD) and influence of the treatment on the level of a daily proteinuria. 25 patients with CKD ІІ and ІІІ stages in a combination with CHD were divided into 2 groups. The first group – 13 patients who received solution L-arginine 4,2% - 100 ml once a day in a complex of basic nephroprotector therapy. The second group – 12 patients who received only nephroprotector therapy. The research demonstrates that addition to basic antihypertensive therapy of sol. L-arginine for intravenous introduction promote function improvement of endothelia functions of vessels for 56,6% and reduction of level of a daily proteinuria by 28,9%.